Acute bee paralysis virus occurs in the Asian honey bee Apis cerana and parasitic mite Tropilaelaps mercedesae - Pichaya Chanpanitkitchote (2018)
© 2017 Elsevier Inc. Viruses, and especially RNA viruses, constantly change and adapt to new host species and vectors, posing a potential threat of new and reemerging infectious diseases. Honey bee Acute bee paralysis virus (ABPV) and Deformed wing virus (DWV) are two of the most common honey bee viruses found in European honey bees Apis mellifera and have been implicated in worldwide Varroa-associated bee colony losses. Previous studies have shown that DWV has jumped hosts several times in history causing infection in multiple host species. In the present study, we show that DWV infection could be detected in the Asian honey bee, A. cerana, and the parasitic mite Tropilaelaps mercedesae, confirming previous findings that DWV is a multi-host pathogen and supporting the notion that the high prevalence of DWV in honey bee host populations could be attributed to the high adaptability of this virus. Furthermore, our study provides the first evidence that ABPV occurs in both A. cerana and T. mercedesae in northern Thailand. The geographical proximity of host species likely played an important role in the initial exposure and the subsequent cross-species transmission of these viruses. Phylogenetic analyses suggest that ABPV might have moved from T. mercedesae to A. mellifera and to A. cerana while DWV might have moved in the opposite direction from A. cerana to A. mellifera and T. mercedesae. This result may reflect the differences in virus life history and virus-host interactions, warranting further investigation of virus transmission, epidemiology, and impacts of virus infections in the new hosts. The results from this study indicate that viral populations will continue to evolve and likely continue to expand host range, increasing the need for effective surveillance and control of virus infections in honey bee populations.